Caracterização do lodo de lagoa anaeróbia tratando resíduos esgotados de tanques sépticos e fossas com vistas ao aproveitamento - Assunção, Marcella de Sá Leitão (2012)
The sludge generated in stabilization ponds can be designed for various purposes, among them we mention agricultural use, recovery of degraded areas and civil construction. The choice of these alternatives should be made based on qualitative and quantitative characteristics of the sludge. In this context, this study characterized the digested sludge from an anaerobic lagoon in Cidade do Natal/RN, which deals exclusively with residues of depleted septic tanks and pits. The sludge showed levels of macro and micronutrients that confirm its potential for agriculture, with 139.49 g.kg -1 organic matter, 15.40 g.kg-1 nitrogen and metal concentrations below those required by Resolution No. 375/06 of CONAMA, besides the absence of fecal coliform and less than 0.15 viable helminthes eggs/g, on average. The particle size distribution showed that most of the particles have a diameter similar to the sand, allowing the replacement of this input, for example. Analysis of the leachate and of the sludge solubilized classified as non-inert and non-hazardous according to NBR 10.004/04. The volume produced in three years of operation by the pond was 1903.50m³, equivalent to approximately 400 kg of dry sludge. Overall, the concentrations of the parameters were similar to literature, although none of them addresses sludge anaerobic pond treating sewer from septic tanks and pits.The sludgepresents technical feasibility to various types of use, however the cost of dewatering and especially with transport can derail it. It needs to be made a more thorough study of the costs to prove its economic viability